Violence during Early Childhood and Child Development - Matias Berthelon; Dante Contreras; Diana Kruger; María Isidora Palma (Institute of Labor Economics (IZA), 2018)
We study the effects of violence towards children on early childhood development. We contribute to the literature providing estimates of the effects of violence (verbal and/or physical) that control for child-mother unobserved characteristics. We find that violence has negative effects on verbal skills (Peabody Picture Vocabulary Test) and socio-emotional development (Child Behavior Check List). We also find that violence affects girls in their vocabulary development and increases behavioral problems of both boys and girls, with stronger effects among boys; that the negative effects diminish as children get older; and that they are more harmful among children with less educated mothers.
Keywords: O15; J12; J13; I31; 330; violence toward children; spanking; corporal punishment; child development; cognitive and socio-emotional outcomes; Chile